Effects of SARS-CoV-2 on Cardiovascular System: The Dual Role of Angiotensin-Converting Enzyme 2 (ACE2) as the Virus Receptor and Homeostasis Regulator-Review - Aleksova, Aneta; Gagno, Giulia; Sinagra, Gianfranco; Beltrami, Antonio Paolo; Janjusevic, Milijana; Ippolito, Giuseppe; Zumla, Alimuddin; Fluca, Alessandra Lucia; Ferro, Federico (International journal of molecular sciences, 2021)
Angiotensin-converting enzyme 2 (ACE2) is the entry receptor for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the cause of Coronavirus Disease-2019 (COVID-19) in humans. ACE-2 is a type I transmembrane metallocarboxypeptidase expressed in vascular endothelial cells, alveolar type 2 lung epithelial cells, renal tubular epithelium, Leydig cells in testes and gastrointestinal tract. ACE2 mediates the interaction between host cells and SARS-CoV-2 spike (S) protein. However, ACE2 is not only a SARS-CoV-2 receptor, but it has also an important homeostatic function regulating renin-angiotensin system (RAS), which is pivotal for both the cardiovascular and immune systems. Therefore, ACE2 is the key link between SARS-CoV-2 infection, cardiovascular diseases (CVDs) and immune response. Susceptibility to SARS-CoV-2 seems to be tightly associated with ACE2 availability, which in turn is determined by genetics, age, gender and comorbidities. Severe COVID-19 is due to an uncontrolled and excessive immune response, which leads to acute respiratory distress syndrome (ARDS) and multi-organ failure. In spite of a lower ACE2 expression on cells surface, patients with CVDs have a higher COVID-19 mortality rate, which is likely driven by the imbalance between ADAM metallopeptidase domain 17 (ADAM17) protein (which is required for cleavage of ACE-2 ectodomain resulting in increased ACE2 shedding), and TMPRSS2 (which is required for spike glycoprotein priming). To date, ACE inhibitors and Angiotensin II Receptor Blockers (ARBs) treatment interruption in patients with chronic comorbidities appears unjustified. The rollout of COVID-19 vaccines provides opportunities to study the effects of different COVID-19 vaccines on ACE2 in patients on treatment with ACEi/ARB.